TENSION-FREE VAGINAL TAPE AND FEMALE STRESS URINARY INCONTINENCE. OUR INITIAL EXPERIENCE IN PAKISTAN - Hameed, Nazli; Ali, M. Asghar (Journal of Ayub Medical College Abbottabad, 2006)
Stress Urinary Incontinence (SUI) is the most common form of urinary incontinence in women. Prevalence of urinary incontinence in women in UK and France is 32%1. Whereas SUI contributes about 13.1% in Asian population, whereas, its prevalence in Pakistan is about 11% (Reported by Asian Society for Female Urology ASFU). In order to rectify the negative impact of SUI on an individual’s quality of life, many modes of treatment have been devised. These include both medical therapy (non pharmacological and pharmacological) and surgical procedures. Surgical treatment offers the highest cure rate (85-90%) when compared to medical options. Surgical treatments include three retropubic procedures: MarshallMarchetti-Kruntz vesicourethral suspension, Burch colposuspension and laparoscopic retropubic repair. One of the newer and less invasive technique is tension free vaginal tape (TVT), introduced for the first time by Ulmsten et al in Europe2. It is a variation of the traditional sling operation that is best suited for SUI patients that have urethral hyper mobility in addition to sphincter insufficiency. Tension free vaginal tape has become increasingly popular with both gynecologists and urologists across Europe. This gold standard technique has been recently introduced in Pakistan. We present a case series of six of our patients of SUI that were successfully treated with TVT at Combined Military Hospital Peshawar.